„Poza wierszem i prozą, poza intencją i uzasadnieniem”. O granicach wierszowości w serii przypisów do utworu Zmieniał się język - Cieślak-Sokołowski, Tomasz (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
The article attempts to outline such a concept of critical reading which would take into consideration the deconstructive practice of American critics, which could be applied to the interpretation of Polish modern poetry. My aim is to present the concept of continuity, rather than schism, between New Criticism (the meaning of a poem cannot be determined, the meaning is ambiguous, paradoxical and ironic, held together by the “organic” unity of the poem) and deconstruction (indeterminacy in the poem is the function of its structure). The reading of Czeslaw Milosz’s poem Zmieniał się język proves to be a convenient field for the above statements.